Peningkatan Kualitas Guru Anak Usia Dini dalam Upaya Pengembangan Sumber Daya Manusia Berkualitas di Masa Depan - Ardipal Ardipal (Fakultas Bahasa dan Seni UNP, 2009)
The aim of early age education is to develop all of student’s basic potential ability. To develop the student’s basic potential ability, it is needed the improvement of teachers’ profesionalism. The improvement of teachers’ profesionalism itself should be done toward both of the guide of profesionalism capability and the guide of commitment. The improvement of profesionalism capability for early age education teachers can be done through: education supervision; certification program and study task; commitment training for early age education teachers by helping their welfare. Key words: early age education, improvement of teachers’ profesionalism